Recreating the Rwandan state and Citizen : an analysis of diaspora politics and its role in transforming Rwandan identities - Ta, Thanh (Department of Political Studies, 2016)
This dissertation utilizes a descriptive case study method to provide a comprehensive and critical analysis of identity politics in Rwanda. More specifically, this thesis situates identity politics in nation building in post-genocide Rwanda. In order to do so, this study examines diaspora engagement politics. The central question in this thesis is: In what ways, and to what extent, have identity politics affected the nation building project in post-genocide Rwanda, in relation to its diaspora? Rwanda's turbulent history raises many issues regarding the political and social construction of Rwandan identity, but scholarship has not thoroughly examined the diaspora and state engagement with the diaspora. This thesis sought to examine these dynamics. It will do so by examining: (1) the ways in which the Rwandan Patriotic Front reconfigured identities inside Rwanda by perpetuating the narrative of unity; (2) the collective identities ascribed to groups of citizens inside and outside Rwanda, based on this government narrative; (3) how the RPF governed perceptions abroad; and finally (4) the education programs to shape the ideal Rwandan citizen. This thesis concludes that the Rwandan government, while trying to rebuild the nation, has failed to transcend divisive identities that have pervaded in Rwanda. Instead, it has created a tightly controlled political space in which a restrictive single identity and narrative existed; furthermore, identity politics have been increasingly manipulated and controlled by the state apparatus. The state's engagement with its diaspora illustrates this.